Politicization of Government Social Media Communication: A Linguistic Framework and Case Study - Nic DePaula; Sten Hansson (Social Media + Society)
Social media communication of government agencies should ideally be truthful and impartial to sustain public trust in government and support democratic goals. However, the politicization of agencies may harm the benefits that impartial and engaged communication brings. In this study, we provide a linguistic framework for analyzing how agency politicization is reflected in the language of government social media communication by asking: How does the agency (1) use speech acts (e.g., commands, requests), (2) talk about itself and others, (3) refer to statistical and scientific information, and (4) express positive and negative sentiment? We demonstrate the application of the framework by conducting a case study of the United States Environmental Protection Agency’s messaging on Twitter across administrations with distinct ideological alignments between the agency and its top administrator. The analysis shows that (1) requests and statistical information were used substantially more under the administrator more aligned with the agency mission; (2) expressive speech acts were used more often during the administration less aligned with the agency mission; and (3) posts were generally positive but more so under the administration less aligned with the agency mission, possibly to counteract increased public criticism. We discuss the results in relation to theories of politicization and government communication, and the implications for citizens and public sector communicators using social media sites.